The Effectiveness of the Implementation of the Two Stay Two Stray (TSTS) Learning Strategy in Elementary Age Children - Trisna Pratiwi Hasibuan (Journal of Contemporary Islamic Primary Education, 2023)
The purpose of this study is to analyze the effectiveness of implementing the two stay two stray learning strategy in elementary age children. This research uses a type of qualitative research with descriptive methods. The results of this study are that the two stay two stray learning strategy is very effective to be applied to elementary age children. Because in implementing this strategy, students are actively involved in the learning process. The children also feel happy when this strategy is implemented in the classroom. That way, as a teacher must be wise in sorting and choosing the appropriate strategy to be applied in teaching and learning activities. So it is hoped that students can more easily understand the material presented by the teacher.